Effectiveness of Planned Teaching Program on Worm Infestation among Parents of Under-five Children at Selected Rural Area of Vadodara - Belagavi, Dayanand; P. Joseph, Rajesh; E.V. , Nirmal Raj; Gamit, Urvashi; Joseph, Miracle; Khatik, Ravi; Gohil, Mittal (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Worm infestation in children is very common in India. Worm infestations are seen in warm and moist climates in tropical and subtropical regions. These infections are more common in under-five period because children of this age group are more likely than others to eat inedible substances 1.Material and Methods: A pre-experimental design with one group pre-test post-test study was conducted among 100 parents of under-five children to assess the effectiveness of a teaching program. Mothers of under-five children were selected by using a convenient sampling technique. The tool consisted of demographic variables of parents and 20 items of a self-structured knowledge questionnaire, which were administered and collected the data, which was then tabulated and analyzed by using descriptive and inferential statistics.Results: The pre-test findings showed that 78% of the parents had average knowledge, 14% had good knowledge, and only 8% had poor knowledge regarding worm infestation. After administration of the planned teaching program, there was marked improvement in post-test knowledge, in which the majority, 81%, of parents gained good knowledge, 15% had very good knowledge, and only 4% had average knowledge. The mean post-test knowledge score (13.63) was higher than the mean pre-test score (8.44), which depicts better efficacy in teaching. There was no significant association found between pre-test knowledge scores and demographic variables.Conclusion: Thus, the planned teaching program had a positive variation in the knowledge about the worm infestation in parents. This may be due to effective teaching skills and the parent’s ability to capture the information while educating. However, they did not recognize any significant association of pretested knowledge scores with demographic data.